A Provincial Perspective of Nonlinear Okun’s Law for Emerging Markets: the Case of South Africa - Kavese , Kambale; Phiri, Andrew (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
A provincial analysis of Okun’s law in South Africa is provided in this article from 1996 to 2016. Empirically, we rely on the nonlinear autoregressive distributive lag (N-ARDL) model whilst the Corbae-Ouliaris filter is used to extract the ’gap’ variables required for our regression estimates. Okun’s law is found to be significant hold in the longrun exclusively for the Western Cape and Kwa-Zulu Natal provinces whereas the remaining provinces partially display significant short-run effects. Our sensitivity analysis in which panel N-ARDL estimations for all provinces finds insignificant long-run Okun effects for the country as a whole, whilst validating the relationship only in the short-run. Our study hence advises that the epicenter of policy efforts in addressing the country’s high unemployment and low economic growth dilemma should be concentrated at a provincial level.